Teachers’ Experiential Strategies for Bridging Writing Proficiency Gaps among Secondary Level Students - Joshi, Dev Ram (Far Western Review, 2024)
The secondary level English curriculum of Nepal aims to enable students to produce various forms of writing items, such as paragraphs, essays, reviews, stories, dialogues, and letters in both personal and academic contexts. However, many students in Nepalese context struggle in the early stages of writing proficiency due to which they are unable to accomplish the competency as targeted by the curriculum. Therefore, this study intends to explore the strategies to bridge the gaps between target of curriculum and proficiency level of students in Nepalese ELT classes by collecting data from secondary level English language teachers through in-depth interview under the framework of hermetic phenomenology and interpreting their lived experiences creating the themes on the basis of broader and specific meaning units. I found that the ecosystem in language teaching created the atmosphere to learn language skills and aspects interactively. Additionally, the theme and genre-based writing activities enabled learners to develop writing skill with proper style and cohesion. This study will be beneficial for those English language teachers who are facing problems of writing proficiency gaps in their students while developing writing skill. With the help of strategies suggested by this study, the teachers can guide students to develop both initially fundamental writing skills and then gradually take them to the level of creative writings to meet the target of curriculum.